Innovative competences in public administration: The path to sustainable development, financial efficiency and strengthening of national security - Zaporozhets, Tetiana; Khomiuk, Nataliia; Hanushchyn, Solomiia; Niema, Oleksandra; Domsha, Olha; Serhieiev, Viacheslav (Edelweiss Applied Science and Technology, 2024)
The article claims that modern transformation processes in the system of international relations have led to the emergence of a new set of security problems threats, challenges, and risks of a non-traditional series, differing from traditional, military-strategic threats in the parameters of their impact on modern states and their transboundary nature. Hybrid dangers have an increasing impact on societal domains. To further their political, ideological, or commercial goals, hybrid actors take advantage of the weaknesses found in intricately interconnected communities. Research makes an attempt to outline innovative competencies of public administration in the domains of national security and sustainable development within this complex environment.